Progress Monitoring in Social Studies Using Vocabulary Matching Curriculum‐Based Measurement. Issue 2 (28th March 2017) - Lembke, Erica S.; Allen, Abigail; Cohen, Daniel; Hubbuch, Chris; Landon, Dorothy; Bess, Joy; Bruns, Heather
Abstract : Two hundred and two (n = 202) sixth‐grade students in social studies were administered a weekly vocabulary‐matching curriculum‐based measure (CBM) for 35 weeks. Students were also administered the Scholastic Reading Inventory (SRI), along with the annual state high‐stakes test in Communication Arts. CBM scores were analyzed with respect to alternate form reliability, validity with criterion measures, and student growth over time. Results suggest that the vocabulary‐matching CBM is reliable and valid with the SRI but not with the state test. Students showed an overall linear trend of growth, but this growth was flat in the middle of the semester. Implications for research and practice are discussed.